Strain on the ICU resources and patient outcomes in the COVID-19 pandemic: A Swedish national registry cohort study. Issue 1 (27th January 2023) - Stattin, Karl; Frithiof, Robert; Hultström, Michael; Lipcsey, Miklos; Kawati, Rafael
Abstract : BACKGROUND: The Coronavirus 2019 (COVID-19) pandemic has led to an unprecedented strain on the ICU resources. It is not known how the ICU resources employed in treating COVID-19 patients are related to inpatient characteristics, use of organ support or mortality. OBJECTIVES: To investigate how the use of ICU resources relate to use of organ support and mortality in COVID-19 patients. DESIGN: A national register-based cohort study. SETTING: All Swedish ICUs from March 2020 to November 2021. PATIENTS: All patients admitted to Swedish ICUs with a primary diagnosis of COVID-19 reported to the national Swedish Intensive Care Register (SIR). MAIN OUTCOME MEASURES: Organ support (mechanical ventilation, noninvasive ventilation, high-flow oxygen therapy, prone positioning, surgical and percutaneous tracheostomy, central venous catheterisation, continuous renal replacement therapy and intermittent haemodialysis), discharge at night, re-admission, transfer and ICU and 30-day mortality. RESULTS: Seven thousand nine hundred and sixty-nine patients had a median age of 63 years, and 70% were men. Median daily census was 167% of habitual census, daily new admissions were 20% of habitual census and the median occupancy was 82%. Census and new admissions were associated with mechanical ventilation, OR 1.37 (95% CI 1.28 to 1.48) and OR 1.44 (95% CI 1.13 to 1.84), respectively, but negatively associated with noninvasive ventilation, OR 0.83 (95% CI 0.77 to 0.89) and OR 0.40 (95% CI 0.30 to 52) and high-flow oxygen therapy, OR 0.72 (95% CI 0.67 to 0.77) and OR 0.77 (95% CI 0.61 to 0.97). Occupancy above 90% of available beds was not associated with mechanical ventilation or noninvasive ventilation, but with high-flow oxygen therapy, OR 1.36 (95% CI 1.21 to 1.53). All measures of pressure on resources were associated with transfer to other hospitals, but none were associated with discharge at night, ICU mortality or 30-day mortality. CONCLUSIONS: Pressure on ICU resources was associated with more invasive respiratory support, indicating that during these times, ICU resources were reserved for sicker patients.